Liquid jet breakup in gaseous crossflow injected through a large diameter nozzle. (June 2023) - Rouaix, Clément; Stoukov, Alexei; Bury, Yannick; Joubert, David; Legendre, Dominique
Abstract: Near nozzle field behavior of round liquid jets injected through large injector diameter (ranging from 0.2 to 0.6 m) into subsonic uniform gaseous crossflows is numerically investigated using the Volume of Fluid (VoF) method. The liquid jet to gas momentum ratio is ranging from 4.3 to 39 with a gas Weber number ranging from 1 . 6 × 1 0 4 to 5 . 3 × 1 0 4 . The large scale liquid water column main properties, such as primary breakup process, liquid column penetration height, liquid column expansion and column breakup point location are studied. Effects of several parameters on the liquid column evolution are investigated, namely the diameter injector, the liquid jet injection velocity and the gaseous crossflow velocity. It has been found that the surface breakup and column breakup mechanisms are both contributing to the liquid column fragmentation. The fragmentation at large scale is characterized by the generation of a significant number of well developed arm and leg structures that align with the airflow on the side and at the bottom of the liquid column. Correlations for the main liquid jet properties are proposed and compared with results previously obtained for smaller size liquid jet. Liquid column penetration height, width and column breakup height follow the same type of power laws that those observed for liquid jet at smaller size. The liquid jet evolution is compared to the water jet generated by the B747 airtanker. Highlights: Numerical Simulations of a liquid jet of large diameter in an air cross flow. Both column and surface breakup are observed. The liquid column deformation is characterized by long leg and arm structures. Liquid jet penetration and transverse expansion follow power law relations. Liquid column evolution consistent with liquid jet generated by the airtanker B747.